1996
DOI: 10.1007/bf00327912
|View full text |Cite
|
Sign up to set email alerts
|

Body size evolution of oxyurid (Nematoda) parasites: the role of hosts

Abstract: Studying the diversification of body size in a taxon of parasites allows comparison of patterns of variation observed in the parasites with patterns found in free-living organisms. The distributions of body size of oxyurid nematodes (obligate parasites of vertebrates and invertebrates) are lognormally right-skewed, except for male oxyurids in invertebrates which show left-skewed distributions. In these parasitic forms, speciose genera do not have the smallest body sizes. Parasite body size is positively correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 35 publications
2
58
1
Order By: Relevance
“…Morand et al (1996) hypothesized and confirmed in the case of endoparasites that long-lived hosts provide more energy and could harbor more long-lived and larger parasites. Therefore, host longevity could represent the predictability connected with specialization.…”
Section: Determinants Of Host Specificitymentioning
confidence: 69%
“…Morand et al (1996) hypothesized and confirmed in the case of endoparasites that long-lived hosts provide more energy and could harbor more long-lived and larger parasites. Therefore, host longevity could represent the predictability connected with specialization.…”
Section: Determinants Of Host Specificitymentioning
confidence: 69%
“…Trouv e et al, 2003;Randhawa & Poulin, 2009;Benesh et al, 2013) and nematodes (e.g. Harvey & Keymer, 1991;Morand et al, 1996;Arneberg et al, 1998) show the expected positive relation between adult helminth size and definitive host body size, acanthocephalans show this pattern only weakly when corrected for phylogeny , and trematodes only when uncorrected for phylogeny (Poulin, 1997(Poulin, , 2007. Further trematode puzzles include failure to find an egg size-number trade-off (Poulin, 1997; but see Loker, 1983), and their similar growth patterns in ectotherm and endotherm definitive hosts (Poulin & Latham, 2003).…”
Section: Future Prospectsmentioning
confidence: 99%
“…In fact, we pointed out a significant correlation between host cell size and the final parasite size. This phenomenon, currently observed in parasitology (39)(40)(41), has been reported just once in the context of the fungal parasitism of phytoplankton (17). Chytrids, like some other parasites, feed on the contents of their host (3), and so their development and final size are closely dependent on these contents.…”
Section: Discussionmentioning
confidence: 75%